The Effect of Electronic Customer Relationship Management on Customer Satisfaction mediated by Customer Experience at Telkomsel Company - Ibrahim Hanif; Maria Apsari Sugiat (Cita konsultindo, 2024)
In today's digital age, the internet significantly influences communication and information access, enabling companies to better understand and measure consumer behavior. This research assesses the influence of Electronic Customer Relationship Management (E-CRM) on customer satisfaction, with Customer Experience acting as an intermediary element. A quantitative, causal approach was employed, with data collected from 385 Telkomsel customers using the MyTelkomsel application. Primary data was gathered through Google Forms, while secondary data was sourced from websites, journals, and previous studies Partial Least Squares (PLS) The data analysis included the use of Structural Equation Modeling (PLS-SEM), which encompassed the Outer Model, Inner Model, and bootstrapping tests. The results indicate that Customer Experience has the greatest impact on boosting Customer Satisfaction at Telkomsel. To enhance Customer Satisfaction, the study suggests that Telkomsel should focus on improving Customer Experience. Future research should consider different industries to facilitate comparative studies.